Catching up with the Vaughn express: Six years of standards-based teacher evaluation and performance pay. - Kellor, Eileen M. (Education Policy Analysis Archives, 2005)
Traditional methods of paying and evaluating teachers in the United States are longstanding, but discussions about changing these systems to support teacher quality and student achievement goals are becoming more common. Efforts to make significant changes to these programs can be difficult and take many years to design, gain approval, and implement; thus, few examples of alternative teacher compensation and evaluation systems exist. Relieved from many of the restrictions and requirements associated with most traditional public school systems, charter schools often are better positioned to implement changes more quickly than a traditional school, yet their experiences can provide useful information for others who are engaging in similar activities. Thus, the experience of a large urban charter school that designed and implemented an innovative teacher compensation system and standards-based teacher evaluation system that has been in place for six years offers important lessons in designing, implementing, evaluating and refining these systems.